Workshop of Thematic Learning for Elementary School Teachers Working Group of Group I Sungai Ambawang Kubu Raya Regency - Sugiyono Sugiyono; Kartono Kartono; Ky Margiaty; Nuri Sidauruk (Universitas Tanjungpura, 2018)
This workshop provides training, manufacture and implementation of thematic lessons for teachers of group I Sungai Ambawang, Kubu Raya Regency conducted with the aim to improve understanding of thematic learning concepts, improve professionalism and ability of teachers in designing learning by using thematic learning as well as improve student learning activities through the implementation of learning by using thematic learning. The results obtained from the workshop activities are enthusiastic participants in following the activities on thematic learning, improving teachers' understanding in designing thematic learning and teacher skills in implementing thematic learning. This is supported by several factors, including the willingness and ability of elementary school teachers group I Sungai Ambawang, Kubu Raya Regency to get thematic lessons, resource persons with professional and experienced skills, and enthusiasm of elementary school teachers in group I Sungai Ambawang, Kubu Raya Regency In the preparation of the implementation plan of learning.